Pengaruh Pencatatan Keuangan, Perencanaan Modal, dan Siklus terhadap Keberlangsungan Usaha Mikto Non-franchise di Desa Margakalih Tarongong Kidul Kabupaten Garut - Sira Aisyah; Heidi Siddiqa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
Although MSMEs are crucial to the economy, the sustainability of non-franchise micro-enterprises is often hampered by suboptimal financial governance. Low utilization of financial information, lack of separation between personal and business finances, and unstructured cash flow management are challenges that can affect long-term business sustainability. This quantitative study aims to evaluate the impact of financial record keeping, capital planning, and cash cycle management on the sustainability of non-franchise micro-enterprises in Mekargalih Village, Garut Regency. Using a survey method and saturated sampling technique, data from 70 business owners were analyzed using multiple linear regression. The results of the study indicate that financial record keeping does not have a significant impact on business sustainability, indicating that recording activities are still administrative in nature and have not been optimally utilized as a basis for business decision-making. Conversely, capital planning and cash cycle management have been shown to have a positive and significant impact on business sustainability. Business owners who are able to plan capital needs and maintain smooth cash flow tend to be more able to maintain the stability of their business operations. Simultaneously, these three variables contribute 45.2% to business sustainability. This finding confirms that the ability to allocate capital andKeywords: business continuity; financial records; capital planning; cash cycle; micro-enterprises.